Widely tunable black phosphorus mid-infrared photodetector - Xiaolong Chen; Xiaobo Lu; Bingchen Deng; Ofer Sinai; Yuchuan Shao; Cheng Li; Shaofan Yuan; Vy Tran; Kenji Watanabe; Takashi Taniguchi; Doron Naveh; Li Yang; et al. (Nature Communications, 2017)
The bandgap of ultrathin black phosphorus can be tuned by a vertical electric field. Here, the authors leverage such electric field to extend the photoresponse of a black phosphorus photodetector to 7.7 μm, opening the doors to various mid-infrared applications.